Qualitative study on the effects of hydroxyl functionalized multiwall carbon nanotube and silica doped‐epoxy composites. Issue 3 (28th December 2021) - Yasaroglu, Inci; Aras, Omur; Kaya, Yunus
Abstract: Epoxy resins have great potential for industrial applications because of their excellent properties such as good adhesion, durability, higher strength, and so forth. But, their high‐viscosity limits industrial usage. Reducing the viscosity with suitable diluents provides an advantage on industrial scale processing, but this also causes a decrease in their chemical and mechanical properties. The production of epoxy‐based composite materials provides good mechanical, heat, and solvent resistance properties. Therefore, determination of additives amount and dilution ratio for specific working area are important for these materials. In this context, this study first includes synthesis of bisphenol A‐based epoxy resin and characterization with fourier transform infrared (FTIR) and nuclear magnetic resonance (NMR) spectroscopy. Second, chemical, mechanical, thermal, and surface properties of the resin were investigated by varying the reactive/nonreactive diluents and additives. Multiwall carbon nanotube (MWCNT‐modified with triton X‐405 nonionic surfactant) and fumed silica as additives were used in this study. Mechanical and chemical tests were applied to 49 types of materials. In order to see the significance levels and synergistic effects of diluents on tensile strength, 3D graphs were obtained with the experimental and modeled data. ANOVA was also performed for significance levels of the diluents. After that, the effects of silica and carbon nanotube additive on tensile strength were investigated. As a result of the tensile test and TGA analysis of the pure epoxy, the ultimate tensile strength was measured as 59.07 MPa, Tg (°C), and Tm (°C) values were found as 175.5 and 304.0°C. These results increased for the nanocomposite material prepared with 2% fumed silica and 0.1% MWCNT (modified YAM) as 81.64 MPa, 192.2 and 333.3°C. It was also shown that the ultimate tensile strength, which decreased with dilution of pure epoxy, could be increased significantly with the additives. Abstract :